Modulation of Aggregation‐Caused Quenching to Aggregation‐Induced Emission: Finding a Biocompatible Polymeric Theranostics Platform for Cancer Therapy. Issue 19 (12th August 2021) - Wang, Cheng; Wang, Ziyu; Chen, Shaoqing; Cui, Pengfei; Qiu, Lin; Zhou, Shuwen; Jiang, Hua; Jiang, Pengju; Wang, Jianhao
Abstract: Dual intramolecular FRET polymers are synthesized via Suzuki coupling and their luminescence characteristics from aggregation‐caused quenching (ACQ) to aggregation‐induced emission (AIE) is modulated conveniently by adjusting the charged ratios. The finally obtained AIE polymer is further employed to construct doxorubicin loaded nanoparticles as a promising theranostics platform for cancer therapy. Abstract : Dual intramolecular fluorescence resonance energy transfer (FRET) polymers are synthesized via Suzuki coupling and their luminescence characteristics from aggregation‐caused quenching (ACQ) to aggregation‐induced emission (AIE) is modulated conveniently by adjusting the charged ratios. The finally obtained AIE polymer is further employed to construct doxorubicin loaded nanoparticles as a promising theranostics platform for cancer therapy.